Effectiveness of Nursing Interventions on the Pain Levels of School-Age Children - A Syamsinar Asmi; Nursyamsi Norma Lalla (Edukasi Ilmiah Indonesia, 2025)
Introduction: Pain is a common issue experienced by school-aged children undergoing invasive procedures such as venipuncture, injection, or catheter insertion. Inadequate pain management may lead to anxiety, fear of hospitals, and long-term behavioral changes. This study aims to determine the effectiveness of nursing interventions in reducing pain levels among school-aged children during invasive procedures. Methods: This research employed a quasi-experimental design with a pre-test and post-test control group. A total of 60 children aged 7–12 years who underwent invasive procedures in a pediatric ward were selected through purposive sampling. The intervention group received non-pharmacological pain management techniques such as deep breathing, distraction, and cold compresses, while the control group received standard care. Pain levels were measured using the Wong-Baker FACES Pain Rating Scale before and after the procedure. Results: The results showed a significant decrease in pain scores in the intervention group compared to the control group (p < 0.05). Children who received the nursing interventions reported lower pain intensity and showed improved coping behaviors during the procedure. Conclusions: Nursing interventions utilizing non-pharmacological techniques are effective in reducing pain levels in school-aged children undergoing invasive procedures. It is suggested that pediatric nurses incorporate these interventions as standard practice to enhance the quality of care and comfort for pediatric patients.